Seismic capacity assessment of cracked lining tunnel based on the pseudo-static method. (March 2020) - Qiu, Wenge; Li, Bingtian; Gong, Lun; Qi, Xingxin; Deng, Zhiheng; Huang, Guang; Hu, Hui
Highlights: A modified pseudo-static evaluation method of seismic capacity of tunnel is developed. A simplified damaged plasticity constitutive model for reinforced concrete is developed. The spandrel cracks have the greatest influence on the seismic capacity of tunnel. Abstract: Crack is one of the most common lining deteriorations, which is generally regarded as an indicator of tunnel safety. The present study investigated the lining cracks of 11 tunnels which are 200 km away from the Longmenshan fault zone. In order to evaluate the seismic capacity of these tunnels with longitudinal cracks in the permanent lining, a modified deformation-based pseudo-static assessment method was developed. The propagation of lining cracks was simulated by a reconstructed damaged plasticity constitutive model of reinforced concrete. The analyses adopted a two-dimensional finite element model and took tunnel depth, initial crack position, and the interaction between soil and lining structures into account. The analysis results showed that the modified evaluation method could simulate the damage process of lining structures under the action of seismic shear wave well. The results also showed that the failure modes of tunnels with cracked permanent lining were different with different burial depth in an earthquake. The cracks in the spandrel had the greatest impact on the seismic capacity of tunnels and should be reinforced in time before the earthquake. In addition, the interaction between the temporary support and permanent lining had little effect on the damage process of linings but had an impact on the damage speed. This study can provide a reference for the safety assessment of cracked lining tunnels in seismically active areas and help to determine the reinforcement measures and time more reasonably.